A RESEARCH ON THE QUALİTY OF BUSİNESS LİFE OF HAİRDRESSERS (Third Sector Social Economic Review, 2023)
Hairdressers are a professional group that is in constant contact with people throughout the day and has a busy working life. The fact that the people working in this group have more working hours and less rest periods, as well as leading a stressful and tiring work life, led to research on their work life quality. The aim of this study is to determine the quality of work life of the employees working in the hairdresser and to determine whether there are differences according to demographic characteristics. For this purpose, the research was conducted with the participation of 80 hairdresser employees working in the province of Bartın and agreeing to participate in the research. The method of the study was determined as an easy sample.The prepared questionnaire was sent to the employees via Google Forms and data was collected. In the study, Çiçek (2005) developed in order to determine the work life quality of hairdresser employees; The ""Quality of Work Life Scale"", of which validity and reliability was made by Aba (2009), was applied.The scale consists of three dimensions. These; business environment, working conditions and services provided dimensions and there are 15 statements in the scale. SPSS package program was used in the analysis of the data obtained in the study. The data obtained from the study were evaluated using descriptive statistical methods. Regression analyzes and manova analysis were performed in line with the established models. Considering the result obtained according to the findings of the study, it can be said that demographic characteristics affect the scale of work life quality. As a result of the Manova analysis, it was determined that the difference between the scores of the working conditions dimension and the services provided dimension according to the age of the participants was significant.
Keywords: Work; Life; Quality; Work Life Quality; Hairdresser.